2012
DOI: 10.1182/blood-2011-04-351965
|View full text |Cite
|
Sign up to set email alerts
|

CIN85 is required for Cbl-mediated regulation of antigen receptor signaling in human B cells

Abstract: IntroductionB-cell receptor (BCR) signaling guides critical cell fate decisions in B cells during ontogeny. 1,2 BCRs can generate tolerogenic signals to purge or silence B cells that bind to self-antigens, and immunogenic signals to expand B cells that are specific for foreign antigens. Thus, BCR signaling must be properly regulated at the various stages of B-cell development, as aberrant regulation of BCR signaling potentially leads to autoimmunity and B-cell malignancies.On BCR ligation by antigens, the Src-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
(94 reference statements)
0
23
2
Order By: Relevance
“…Recent studies using Hela, Hep2, B lymphoma cell line BJAB and porcine aortic endothelial cell lines have arrived at a similar conclusion using a CIN85 knockdown approach (Niiro et al 2012; Ronning et al 2011; Schroeder et al 2010; Schroeder et al 2012). …”
Section: Discussionmentioning
confidence: 64%
“…Recent studies using Hela, Hep2, B lymphoma cell line BJAB and porcine aortic endothelial cell lines have arrived at a similar conclusion using a CIN85 knockdown approach (Niiro et al 2012; Ronning et al 2011; Schroeder et al 2010; Schroeder et al 2012). …”
Section: Discussionmentioning
confidence: 64%
“…One could imagine that interactions between the cSH2 domain of PLC-γ2 and Syk and Btk act to stabilize the complex consisting of the BCR, pSyk, pBLNK, pPLC-γ2, and pBtk. We observed that Cbl, an inhibitor of PLC-γ2 (39), was aberrantly colocalized with the BCR in B cells expressing Δ20–22 PLC-γ2, but not in B cells expressing wild-type PLC-γ2. The altered association of Cbl with the BCR could affect PLC-γ2 activity by targeting Syk for ubiquitination and degradation, a function we previously described for Cbl (41).…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, in human B cells, the Cbl-interacting protein of 85 kD (CIN85) constitutively associates with Cbl and BLNK, and functions to increase the phosphorylation of Cbl, which results in decreased phosphorylation of PLC-γ2 and inhibition of Ca 2+ flux (39). These observations raised the possibility that the failure of BLNK to form a stable complex with Syk, Btk, and PLC-γ2 directly or indirectly enables the increased association of Cbl with BLNK, further inhibiting PLC-γ2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…mRNAs were then extracted from cells and reverse transcribed to cDNA as described previously. 12 The mRNA levels were quantified in triplicate using a real-time PCR (Applied Biosystems, Japan, Tokyo). β2-Microglobulin mRNA separately amplified in the same plate was used for internal control.…”
Section: Cfu Assaysmentioning
confidence: 99%